Impacts of Land Cover Change Caused by Urbanization on the Flood Regime of Msimbazi Catchment in Dar es Salaam, Tanzania - Kibugu, Chrisogonous P.; Munishi, Subira; Kongo, Victor (Tanzania Journal of Engineering and Technology, 2022)
The hydrological processes of a catchment are the function of climate, land use and land cover. Changes in either climate or land use or land cover can result in alteration of the catchment ' s hydrological processes. In the recent past, Msimbazi catchment in Dar es Salaam has undergone drastic land cover changes mainly due to urbanisation. These land cover changes caused changes in the behaviour of river flow resulting in frequent floods. Therefore, this study analyses the impacts of the changes in land cover due to urbanisation specifically with the changes in river flow, surface run-off and base-flows. Previously generated land cover maps of Msimbazi catchment and a combination of spatial and meteorological climate datasets were used to parameterise the hydrological model (SWAT). The model was calibrated and validated using the Sequential Uncertainty Fitting algorithm (SUFI-2) on a monthly resolution. The results show that there is an increase in surface run-off, mean river flow and the reduction of base-flow with the increase in urbanisation within the catchment. These increase in river flows, surface run-off and reduction of base-flow indicates the likelihood of an increase in flooding events in the catchment. Keywords: Flash floods, Hydrological modelling, Land use and land cover change, Msimbazi catchment, Soil Water Assessment Tool (SWAT).